2006
DOI: 10.1021/jo0600914
|View full text |Cite
|
Sign up to set email alerts
|

Basic Ionic Liquid as Catalysis and Reaction Medium:  A Novel and Green Protocol for the Markovnikov Addition of N-Heterocycles to Vinyl Esters, Using a Task-Specific Ionic Liquid, [bmIm]OH

Abstract: A basic ionic liquid, 1-methyl-3-butylimidazolium hydroxide ([bmIm]OH), has been introduced as a catalyst and reaction medium for the Markovnikov addition of N-heterocycles to vinyl esters under mild conditions. The evidence for the role of this basic ionic liquid [bmIm]OH in promoting the Markovnikov addition has been given. On the basis of the evidence, a mechanism was postulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(48 citation statements)
references
References 29 publications
3
44
1
Order By: Relevance
“…Various schemes were employed to separate the nucleophile from the metal cation, but even strong bases such as the crown ether are not very good for that purpose. Ionic liquids and molten salts [16][17][18][19][20][21][22][23][24] have recently been found to be quite useful for some organic reactions. For example, D'Anna and co-workers found that in S N Ar reactions amines react faster in ionic liquids than in molecular solvents by almost 1 or 3 orders of magnitude.…”
Section: -15mentioning
confidence: 99%
See 1 more Smart Citation
“…Various schemes were employed to separate the nucleophile from the metal cation, but even strong bases such as the crown ether are not very good for that purpose. Ionic liquids and molten salts [16][17][18][19][20][21][22][23][24] have recently been found to be quite useful for some organic reactions. For example, D'Anna and co-workers found that in S N Ar reactions amines react faster in ionic liquids than in molecular solvents by almost 1 or 3 orders of magnitude.…”
Section: -15mentioning
confidence: 99%
“…There are also situations in which the S N Ar reactions are much more advantageous. For example, the S N Ar procedure is known to be far more selective than electrophilic substitution for producing highly specific 18 F compounds to be used as noninvasive imaging agents to study and probe the molecular and biological processes in living systems with positron emission tomography (PET).…”
Section: Introductionmentioning
confidence: 99%
“…However, the ability of an ionic liquid as a clean catalyst and reagent has not been explored to any great extent although it is of much importance in the context of the green synthesis [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…3-Benzyl substituted 4-hydroxycoumarin derivatives are components of numerous natural products like warfarin, phenprocoumon, coumatetralyl, carbochromen, bromadialone, etc. These compounds also exhibit a wide band of biological activities including antibacterial, anti-HIV [7], antiviral [8], anticoagulant [9], antioxidant [10] and anticancer activities [11]. The vast biological significance of the amino derivatives of 4-hydroxycoumarin inspired us to develop a novel protocol for the efficient synthesis of new benzylamine coumarin derivatives.…”
Section: Introductionmentioning
confidence: 99%